Cerebrolysin improves symptoms and delays progression in patients with alzheimer's disease and vascular dementia - Allegri, Ricardo Francisco (2012)
Dementia is the result of various cerebral disorders, leading to an acquired loss of memory and impaired cognitive ability. The most common forms are Alzheimer´s disease(AD) and vascular dementia (VaD). Neurotrophic factors are essential for the survival and differentiation of developing neurons and protecting them against damage under pathologic conditions. Cerebrolysin is a peptide preparation that mimics the pleiotropic effects of neurotrophic factors Several clinical trials investigating the therapeutic efficacy of Cerebrolysin in AD and VaD have confirmed the proof of concept. The results of these trials have shown statistically significant and clinically relevant treatment effects of Cerebrolysin on cognitive, global and functional domains in mild to moderately severe stages of dementia. Doses of 10 and 30 mL were the most effective, but higher doses of up to 60 mL turned out to be most effective in improving neuropsychiatric symptoms, which become relevant at later stages of the disease. Combining treatment with cholinesterase inhibitors and Cerebrolysin indicated long-term synergistic treatment effects in mild to moderate AD. The efficacy of Cerebrolysin persisted for up to several months after treatment suggesting Cerebrolysin has not merely symptomatic benefits, but a disease-delaying potential. This paper reviews the clinical efficacy of Cerebrolysin in the treatment of dementia. Data were obtained from international, multicenter, randomized clinical trials performed in compliance with Good Clinical Practice and the principles of the Declaration of Helsinki (1964) and subsequent revisions.